KOMUNIKASI ANTARA ORANG TUA DAN ANAK TERHADAP PEMBENTUKAN SIKAP BERSOSIALISASI DI DESA SIGUMURU - Vitria Larseman Dela; Nila Sari; Nor Mita Ika Saputri (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
Parental communication is an important factor for establishing good relations between children and parents. Parental communication has the effect of forming attitudes, opinions, behavior or social formation. Communication between parents and children symbol of the fabric of attention and affection between the two, which with the communication of a child will feel the attention of his parents. Qualitative research methods. Data analysis techniques are inductive and sustainable, concepts and the construction of a new theory. Based on the results of research from interviews conducted by Didesa Sigumuru, the conclusion of this study is that communication between parents and children has become a necessity that must be met in daily life, where the most important thing that is needed by a child is the fabric of good and quality communication will form a more open attitude towards his family, and vice versa if there is no good and quality communication established it will form a more closed attitude.